Effect of rapid weight loss on performance in combat sport male athletes: does adaptation to chronic weight cycling play a role? - Mendes, S. H.; Tritto, A. C.; Guilherme, J. P. L. F.; Solis, M. Y.; Vieira, D. E.; Franchini, E.; Lancha Jr, A. H.; Artioli, G. G. (British Journal of Sports Medicine, 2013)
Background: Studies failing to show a negative effect of rapid weight loss (RWL) on performance have been conducted in athletes who have been cycling weight for years. It has been suggested that chronic weight cycling could lead combat athletes to become resistant to the stresses associated with weight loss. To investigate the effects of RWL up to 5% of body mass on high-intensity intermittent performance in weight cyclers (WC) and non-weight cyclers (non-WC).